PEDIATRIC EDUCATION SPECIAL SERIES Description and Outcomes of a Practicum Model for Experiential Learning in Pediatrics. Issue 3 (2017) - Moerchen, Victoria A.; Dietrich, Margaret; Dietrich, Ann
Abstract : Background and Purpose. : Experiential learning has recently been proposed as essential to pediatric physical therapist (PT) education, but the paucity of evidence for models of experiential learning in physical therapy challenges pediatric educators' ability to respond to this proposal. The purpose of this methods report is to describe the design and outcomes of a short embedded pediatric practicum model that achieves the cognitive‐affective processes of experiential learning. Method/Model Description and Evaluation. : The model described is team‐based and uses a problem‐based learning design to support extended and structured reflective process. It is also designed to address many of the constraints to experiential learning identified within pediatric education. A mixed methods approach was used to examine 3 sources of student self‐evaluation and reflection data from 6 cohorts of students, including 14 student teams and 134 students. Outcomes. : Superordinate themes identified included value and understanding of family‐centered care, learning to see a patient as a whole person, realizing that optimal treatment is individualized and patient‐centered, noting improved communication, and learning to value cooperative learning. Discussion and Conclusions. : The pediatric practicum model proposed and examined in this report provides an example of a feasible experiential learning model that provides an opportunity for cognitiveaffective learning related to client‐/family‐centered care. This model would be generalizable beyond pediatrics.